2003
DOI: 10.1002/path.1361
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of Patched‐associated rhabdomyosarcoma

Abstract: Mutations in the human homologue of Drosophila Patched1 (PTCH1) have been found in several common tumours including basal cell carcinoma, medulloblastoma, and rhabdomyosarcoma (RMS). Medulloblastoma and RMS are also present in the murine model for Ptch1 deficiency. Tumours in heterozygous Ptch1(neo67/+) mice consistently exhibit elevated transcript levels of the proto-oncogene Gli1, of Ptch1 itself, and of the insulin-like growth factor 2 (Igf2). The present study has investigated additional molecular changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0
11

Year Published

2004
2004
2010
2010

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 27 publications
2
24
0
11
Order By: Relevance
“…Semi-quantitative reverse transcription-polymerase chain reaction (RT-PCR) revealed that Gli1 message was expressed at higher levels than Gli2 in primary tumor tissue (Supplementary Figure 1). This is consistent with previous characterizations of elevated Hh pathway activity and Gli1 expression in Ptch1 þ /À rhabdomyosarcomas (Hahn et al, 1998;Kappler et al, 2003).…”
Section: Myogenic Cell Lines Derived From Hip1supporting
confidence: 93%
“…Semi-quantitative reverse transcription-polymerase chain reaction (RT-PCR) revealed that Gli1 message was expressed at higher levels than Gli2 in primary tumor tissue (Supplementary Figure 1). This is consistent with previous characterizations of elevated Hh pathway activity and Gli1 expression in Ptch1 þ /À rhabdomyosarcomas (Hahn et al, 1998;Kappler et al, 2003).…”
Section: Myogenic Cell Lines Derived From Hip1supporting
confidence: 93%
“…Third, the relative abundance of genes such as Igf2, Foxf1, Gadd45a and Cav3 in RMS of heterozygous Ptch1 neo67/ þ mice in comparison to tumors of p53 þ /À mice is consistent with their involvement in Hedgehog/ Patched signaling (Hahn et al, 2000;Karpen et al, 2001;Kappler et al, 2003Kappler et al, , 2004. It has previously been described that Igf2 is highly expressed in RMS of heterozygous Ptch1 neo67/ þ mice, and that it is indispensable for tumor formation (Hahn et al, 2000).…”
Section: Discussionmentioning
confidence: 52%
“…Next, we stained for desmin, a widely used marker for RMS (Coindre, 2003), and found strong expression in all tumors examined, with desminpositive cells more prevalent in p53-dependent RMS. In addition, we stained for the antiapoptotic protein Bcl-2, which has recently been shown to be strongly expressed in 36% of human RMS, as well as in all cases of murine Ptch1-associated RMS (Boman et al, 1997;Kappler et al, 2003). We found high levels of Bcl-2 protein in RMS from both Ptch1 neo67/ þ and p53 þ /À mice.…”
Section: Ptch1-and P53-dependent Rms Differ Extremely In the Time Of mentioning
confidence: 69%
See 2 more Smart Citations